ADVANTAGES AND DISADVANTAGES OF ONLINE TRAINING - Marín Díaz, Verónica (2013)
The technological changes that society, in general, and,education in particular, have beenexperiencing demand that all levels of the education system be renovated. The emergencerenovationof a traditional education system such as distance education has become increasinglyimportant each day if we take into account all the aspects involved in how people learn. elowwe explain why we believe that online training, learning through networks or e-learning shouldbe considered as a tool that provides a new way of seeing, feeling and understanding universityeducation.